Academic and Behavior Combined Support: Evaluation of an integrated supplemental intervention for early elementary students. (December 2021) - Gettinger, Maribeth; Kratochwill, Thomas R.; Eubanks, Abigail; Foy, Alison; Levin, Joel R.
Abstract: In current multi-tier models, students who are not responsive to universal instruction receive supplementary support. Despite most students having co-occurring academic and behavior challenges, their needs are often addressed through separate academic or behavior interventions. This approach may not only be costly for schools, but it also fails to acknowledge the well-documented link between behavior and academic performance. The purpose of this study was to evaluate Academic and Behavior Combined Support ( ABC Support ), a newly developed supplemental intervention that merges a combined focus on reading fluency and engagement. Six teachers implemented the intervention for 6–8 weeks with Grade 2 students. Students' oral fluency on standard and training reading passages and occurrence of engagement and disruptive behaviors during classroom reading instruction were measured repeatedly across baseline and intervention phases in a multiple-baseline design. Visual and statistical analyses revealed significant improvement from baseline to intervention for both reading and behavior outcomes. Post-intervention surveys and interviews revealed a high level of acceptability among teachers and students. Theoretical and empirical contributions as well as practice implications are addressed.